New Caledonian rovers and the historical biogeography of a hyper-diverse endemic lineage of South Pacific leaf beetles - Platania L; Cardoso A; Anderson M; Fikáček M; Gauthier J; Hendrich L; Mille C; Morii Y; Reid CAM; Seidel M; Morgan-Richards M; Trewick SA; et al. (John Wiley & Sons Ltd on behalf of Royal Entomological Society, 2024)
South Pacific archipelagos are central in the biogeographic debate on the relative importance of vicariance and dispersal in shaping the distribution of species. However, each taxonomic group was subject to different processes and histories, and here, we reveal the historical biogeography of the diverse Eumolpinae leaf beetles, widely distributed in the region. Extensive taxon sampling focusing on South Pacific Eumolpinae was used to infer the first molecular phylogeny of the group using three single-copy protein-coding nuclear and two mitochondrial markers. Upon assessing the clade of interest for lineage-specific variation in substitution rates, the age of the most recent common ancestors was estimated using out-group calibration and multi-gamma site models (MGSMs). Biogeographic analyses used standard event-based inferences also incorporating phylogenetic uncertainty. Zealandian Eumolpinae are monophyletic and appear to have split from their global relatives in the transition from the Cretaceous to the Paleogene. Variation in the rates of molecular evolution affected the in-group stem branch, with a significant drop in the substitution rate, and the MGSM correction recovered the crown age of Zealandian Eumolpinae during the Late Eocene–Oligocene transition. Biogeographic inference resolved the origin of the radiation in New Caledonia, favouring a null model without island age constraints, and repeated dispersal events to the other islands, including three independent but synchronous colonisations of New Zealand during the Miocene. New Caledonia, with a highly diverse Eumolpinae fauna of uncertain origin, acted as a hub and pump of biodiversity of these beetles in the entire South Pacific region, sending migrants to other islands through long-distance dispersal with lineages establishing when land became available.
Keywords: Chrysomelidae-Eumolpinae; heterotachy; long-distance dispersa; New Zealand; Zealandia